Comparative proteomic analysis reveals the effects of different fatty acid forms on high-fat diet mice - Jiaping Pan; Huan Wang; Ye Li; Chenyang Lu (Food Science and Human Wellness)
Long-chain omega-3 polyunsaturated fatty acids (LC-PUFAs), known for having many health benefits, are usually present in three forms: triglycerides (TG), ethyl esters (EE), and phospholipid (PL). In this study, the effects of these three LC-PUFAs forms (fish oil for TG and EE, krill oil for PL) on the obese mice were compared, and the proteomic changes that focused on lipid metabolism were evaluated via label-free quantitative proteomics analysis. Compared with the model group, all three of the LC-PUFA form supplementations (labeled as the FO-TG group, FO-EE group and KO-PL groups) could significantly reduce body weight gain (P < 0.01). Low-density lipoprotein cholesterol levels were significantly decreased, whereas high-density lipoprotein cholesterol levels were significantly increased in the FO-TG group and FO-EE group (P < 0.01), and especially in the PL group (P < 0.001). Furthermore, proteomics analysis results suggested that some differentially expressed genes involved in the fatty acid degradation and oxidation pathways had a higher expression fold in the KO-PL group than in the FO-TG or FO-EE groups. Our results showed that dietary LC-PUFAs can reduce fat deposition and inhibit lipogenesis in the liver by upregulating the expression of proteins that are involved in the fatty acid degradation and oxidation pathways. Additionally, KO-PL elicits stronger effects than FO-TG or FO-EE.